2012
DOI: 10.1177/0091270011417716
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran Etexilate in Atrial Fibrillation Patients With Severe Renal Impairment: Dose Identification Using Pharmacokinetic Modeling and Simulation

Abstract: Dabigatran, administered orally as the prodrug dabigatran etexilate (DE), is a direct thrombin inhibitor shown to be effective in the prevention of stroke and systemic embolism in patients with atrial fibrillation (AF). The aim of this analysis was to derive a modeling and simulation-based dose and dosing regimen for AF patients with severe renal failure who could potentially benefit from the use of DE. The exposure was simulated for AF patients with severe renal impairment for several combinations of doses (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 12 publications
(22 reference statements)
2
57
0
3
Order By: Relevance
“…12 However, dose-identification studies (confirmed and supported by the US Food and Drug Administration's clinical pharmacology division) that used pharmacokinetic modeling and simulation have been performed that showed that dabigatran 75 mg BID was a recommended dose in patients with severe renal dysfunction (eGFR 15-30 mL/min). 24 Because the present study was not dimensioned for subgroup analysis, statistical power was relatively low for testing interactions, and a nonsignificant result does not rule out the possibility of treatment heterogeneity. A total of 162 patients had missing creatinine samples, although annual event rates in participants with available measurements were almost identical to the main trial results.…”
Section: Study Limitationsmentioning
confidence: 87%
“…12 However, dose-identification studies (confirmed and supported by the US Food and Drug Administration's clinical pharmacology division) that used pharmacokinetic modeling and simulation have been performed that showed that dabigatran 75 mg BID was a recommended dose in patients with severe renal dysfunction (eGFR 15-30 mL/min). 24 Because the present study was not dimensioned for subgroup analysis, statistical power was relatively low for testing interactions, and a nonsignificant result does not rule out the possibility of treatment heterogeneity. A total of 162 patients had missing creatinine samples, although annual event rates in participants with available measurements were almost identical to the main trial results.…”
Section: Study Limitationsmentioning
confidence: 87%
“…In another study, dabigatran plasma concentrations obtained during the RE-LY trial were analyzed in a pharmacokinetic simulation model, and the relationship between CL CR and dabigatran exposure was found to be nonlinear. 16 Various regimens including 75 mg twice daily, 110 mg daily, and 150 mg daily in patients with a CL CR between 15 and 30 mL/min were expected to have similar drug exposure to that found among healthy subjects. Without any clinical data, the dose of 75 mg twice daily was chosen based on a lower peak-trough ratio than any single daily regimen and similar posology for all patient subgroups which might reduce medication errors and avoid a negative impact on adherence.…”
Section: Renal Impairmentmentioning
confidence: 98%
“…Without any clinical data, the dose of 75 mg twice daily was chosen based on a lower peak-trough ratio than any single daily regimen and similar posology for all patient subgroups which might reduce medication errors and avoid a negative impact on adherence. 16,17 …”
Section: Renal Impairmentmentioning
confidence: 99%
“… Note: Data from previous studies 6,7,46

Abbreviations: T max , time to maximum concentration; PPB, plasma protein binding; t ½ , half-life; F , bioavailability.

…”
Section: Tablementioning
confidence: 99%